2019
DOI: 10.1007/s41042-019-00016-5
|View full text |Cite
|
Sign up to set email alerts
|

Positive Work: A Multidimensional Overview and Analysis of Work-Related Drivers of Wellbeing

Abstract: Scholars are beginning to better appreciate the wide range of work-related 'drivers' of wellbeing (i.e., the ways in which work may promote or hinder employees' wellbeing). This paper brings a multidimensional perspective to bear on this topic by providing a multidimensional overview of these drivers, together with an analysis of how they may actually 'drive' wellbeing. The paper is in two parts. Part 1 briefly summarises the drivers, highlighting key theories and interventions. Part 2 then brings a multidimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 142 publications
0
16
0
Order By: Relevance
“…We propose that locus of control and psychological capital are psychological resources that enable individuals in different employment statuses to maintain high levels of psychological wellbeing. Such psychological strengths are important to drivers of psychological wellbeing (Lomas, 2019 ; Munoz et al, 2016 ). Psychological capital and particularly internal locus of control are constructs within positive psychology that reflect individual differences in response to events and contexts, therefore important for eudaimonic wellbeing.…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
“…We propose that locus of control and psychological capital are psychological resources that enable individuals in different employment statuses to maintain high levels of psychological wellbeing. Such psychological strengths are important to drivers of psychological wellbeing (Lomas, 2019 ; Munoz et al, 2016 ). Psychological capital and particularly internal locus of control are constructs within positive psychology that reflect individual differences in response to events and contexts, therefore important for eudaimonic wellbeing.…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
“…For example, by finding a way to express a micro-act such as foot-dragging (Scott, 1990), a person might be expressing the only modicum of autonomy they feel they have in such a precarious work setting. To bring a more nuanced analysis of the contextual features of academe and how they impact wellbeing at work, we summarise how some of the contextual features undermine the positive drivers of wellbeing at work (Lomas, 2019) (see Table 1). Emotions: Expectations to self-manage own pain, discomfort, and mental health concernsoften framed and silenced by the 'self-care' agenda (Smith and Ulus, 2019).…”
Section: And Thatmentioning
confidence: 99%
“…Indeed, across academe, there have been heterogeneous experiences in relation to the way COVID-19 has impacted academic workloads and the ways in which universities have adjusted workloads, schedules, and compensation for the additional time spent on teaching activity (McKie, 2020). Here, some might read and interpret the email as expressing a genuine and intense, personal caring for colleagues which might generate feelings of reward and recognition for the radical adjustment to new ways of worksa driver of wellbeing at work (Lomas, 2019). However, there are many reports in the media about how academics have struggled to work at home and juggle loneliness, children and other caring responsibilities, illness, domestic tasks and other challenges with a brutal workload, and with no institutional support -leaving them to selfmanage their own distress (Smith and Ulus, 2019).…”
Section: "Love* and Kisses"mentioning
confidence: 99%
“…Personal agency, autonomy, and control are considered drivers of well-being ( 39 ). For instance, a survey of nearly 250 academic radiologists revealed that lack of autonomy was associated with high rates of burnout ( 40 ). We must make our choices carefully and with intention.…”
Section: Introductionmentioning
confidence: 99%